Therapeutic approaches for the treatment of bovine metritis: a systematic review of clinical, reproductive and productive outcomes - Lorenza Frattina; Alice Carbonari; Giovanni Bramante; Matteo Burgio; Olga Maria Andriulo; Vincenzo Cicirelli; Pasquale De Palo; Luis Angel Quintela Arias; Annalisa Rizzo (Theriogenology, 2026)

The NeuroWES project: lessons learned from comprehensive phenotyping and genetic analysis of neurodevelopmental disorders over a decade - Simona Cardaropoli; Lisa Pavinato; Slavica Trajkova; Diana Carli; Verdiana Pullano; Flavia Palermo; Alessandro Mussa; Elisa Biamino; Vincenzo Antona; Andrea Zonta; Paola Dimartino; Mariia Zadorozhna; et al. (Human Genetics, 2026)
Exome sequencing (ES) has become a primary tool for diagnosing neurodevelopmental disorders (NDDs), yet the interpretation of genetic variants in large, heterogeneous cohorts presents significant challenges that automated pipelines often fail to resolve. This study showcases the complexities and novel findings derived from a decade-long analysis of 419 Italian NDD patient-parent trios. While ES established a molecular diagnosis in 36.5% of cases (53.8% in syndromic presentations), our investigation moves beyond diagnostic yield to highlight the critical value of manual curation integrated with deep phenotyping. We demonstrate how this rigorous approach uncovers complex disease mechanisms, revealing that variants initially misclassified as missense or stop-gain are, in fact, pathogenic splicing defects confirmed by functional analysis. Furthermore, we resolve the paradox of pathogenic truncating PPM1D variants in control databases by demonstrating their somatic mosaic nature, a crucial insight for population data interpretation. Our work also refines gene-disease correlations by challenging the established role of MID2 in NDDs, providing further evidence for DSCAM as a high-confidence risk gene, and expanding the known phenotypic spectrum of disorders, such as a novel GNAI2 -related syndrome lacking expected immune dysfunction. This study underscores that navigating the complexities of large NDD cohorts requires a detailed, expert-driven approach to not only enhance diagnostic yield but also to advance our fundamental understanding of rare disease genetics.

Preliminary study on the inflammatory response of Spanish native cattle breed during transition period - Federica Arrigo; Maria Rizzo; Giulia Sisia; Giuseppe Piccione; Claudia Giannetto; Jacobo Álvarez; Renato Barrionuevo; Luis A. Quintela; Francesca Arfuso (Veterinary Immunology and Immunopathology, 2026)

Cytotoxic and genotoxic effects of oxime β-lapachone in human cancer cells: selectivity toward NCI-H460 and insights from molecular docking - Maria Francilene Souza Silva; Lara Polyana Silva Ramos; Fátima de Cássia Evangelista de Oliveira; Bruno Marques Soares; Daniel Pascoalino Pinheiro; Igor Frederico da Silveira Ramos; Rayran Walter Sousa; Victória Laysna dos Anjos Santos; Arlan de Assis Gonsalves; Paulo Michel Pinheiro Ferreira; Heurison Sousa e Silva; Cleônia Roberta de Melo Araújo; et al. (Human Cell, 2026)
β-Lapachone exhibits potent anticancer activity although its clinical application remains limited by toxicity and mechanisms of resistance. Therefore, structural modifications have been explored to improve its pharmacological profile. This study evaluated the cytotoxic, genotoxic, and toxicological effects of the oxime derivative β-lapachone oxime (Oxβ-Lp), together with its predicted pharmacokinetic properties and potential molecular interactions. Oxβ-Lp displayed cytotoxic activity against all tested cancer cell lines (NCI-H460, PC9, K562, and HepG2) after 72 h of exposure, with the greatest potency and selectivity observed in NCI-H460 non-small cell lung cancer cells (IC₅₀ = 1.88 µM; SI = 13.1). Mechanistic analyses demonstrated reduced cell viability, mitochondrial membrane depolarization, DNA damage, and induction of apoptosis, without significant cell cycle arrest. In Allium cepa , Oxβ-Lp did not alter the mitotic index or induce micronucleus formation but promoted chromosomal aberrations and DNA strand breaks. The Artemia salina assay indicated high acute toxicity (LC₅₀ = 16.80 µg/mL). Molecular docking suggested a potential interaction between Oxβ-Lp and NQO1, with binding energies comparable to those of dicoumarol and similar interaction patterns within the catalytic site. Overall, these findings demonstrate that Oxβ-Lp exhibits selective cytotoxicity against NCI-H460 cells and promotes apoptosis associated with mitochondrial dysfunction and DNA damage. Although the molecular mechanisms underlying its biological activity require further investigation, Oxβ-Lp represents a promising scaffold for developing novel anticancer agents.

Hair Metals and Essential Trace Element Profiles in Children With Autism Spectrum Disorder (F84.0): an Exploratory Case-Control Study With Sex Stratified Descriptive Analyses - Renata Rizzo; Tommaso Filippini; Chiara Copat; Alfina Grasso; Eliana Pellegrino; Valentina Crisafi; Andrea Moscato; Margherita Ferrante; Rita Barone; Maria Fiore (Biological Trace Element Research, 2026)
This is an exploratory case–control study assessed levels of metals and essential trace elements in hair samples from children with Autism Spectrum Disorder (ASD) and neurotypical controls, exploring potential differences according to sex. A total of 154 children (61 children with ASD and 93 controls) aged 4–18 years were enrolled at the same clinical site in Eastern Sicily. Demographic, perinatal, dietary, and exposure information was collected through structured parental questionnaires. Hair samples were analyzed using inductively coupled plasma mass spectrometry. Children with ASD showed distinct elemental patterns. Females with ASD had higher median nickel (0.25 vs.0.20 µg/g), lead (1.11 vs.0.55 µg/g), chromium (0.87 vs.0.49 µg/g), and aluminum (10.27 vs. 6.97 µg/g) compared with female controls; similar but smaller differences appeared in males. Mercury levels were consistently lower in children with ASD for both sexes (females: 0.25 vs.0.60 µg/g; males: 0.30 vs.0.58 µg/g). Essential trace elements were markedly elevated in children with ASD: zinc reached 132 µg/g in ASD females vs. 83 µg/g in controls, and 129 vs. 65 µg/g in males; selenium and copper were also higher across sexes. Maternal and child characteristics differed between groups. Mothers of children with ASD reported more infections (30.9% vs. 9.6%) and therapies during pregnancy (43.9% vs.22.6%), while children with ASD showed more gastric disorders (40.4%vs.9.4%), specific diets (21.1% vs.3.5%), and vitamin use (26.3% vs.3.5%). Findings suggest sex-related differences in hair metals and trace elements profiles among children with ASD. The low mercury levels observed in children with ASD showld be interpreted with caution, given that factors such as dietary habits, supplement intake, or differences in metal metabolism were not directly assessed in this study.

Seasonal dynamics of prokaryotic community in Arctic sediments of the Pasvik River by multiplex antibody microarray profiling - Gabriella Caruso; Victor Parro; Mercedes Moreno-Paz; Carmen Rizzo; Alessandro Cosenza; Angelina Lo Giudice; Maria Papale; Maurizio Azzaro (Journal of Environmental Sciences, 2026)

Seasonal variation in metal concentrations in the Gualaxo do Norte River following the Fundão dam collapse is associated with behavioural and cholinergic alterations in Astyanax lacustris - João Victor Saraiva Raimondi Lopes; Cristiano Schetini de Azevedo; Alessandro Loureiro Paschoalini; Thais Victória Pires de Almeida; Maria Eduarda Moura de Morais; Mateus Augusto Silva Diniz; Elizete Rizzo; Angélica da Silva Vasconcellos (Science of The Total Environment, 2026)

Administration of antioxidants at parturition in Italian Mediterranean lactating buffaloes: findings in the postpartum - Lorenza Frattina; Alice Carbonari; Matteo Burgio; Giovanni Bramante; Olga Maria Andriulo; Edmondo Ceci; Ciro Galdieri; Antonietta D’Onghia; Vincenzo Cicirelli; Annalisa Rizzo (Tropical Animal Health and Production, 2026)
The transition period is an extremely critical phase for the Mediterranean lactating buffaloes, characterized by a state of oxidative stress. Oral administration of antioxidants is common. However, the aim of this study was to evaluate whether the intramuscular administration of a vitamin combination, containing α-tocopherol and β-carotene, could improve both milk quality and reproductive performance. The animals were divided into two groups: a group treated, at 24 h postpartum, with a vitamin combination (group D) and a control group (C). For milk quality, concentrations of retinol, α-tocopherol, fat, protein, lactose, Somatic Cell Count (SCC), non-fat dry matter (NFDM), casein, urea, pH, satured fatty acids (SFA), unsaturated fatty acids (UFA), monounsaturated fatty acids (MUFA) and poliunsaturated fatty acids (PUFA) in milk were assessed at 7 and 30 days post-treatment. Reproductive performance was evaluated using two parameters: pregnancy rate and the calving-conception interval. Retinol concentrations did not differ significantly between groups or across time points. α-tocopherol levels were significantly higher in group D compared to group C at T30 (0.35 ± 0.016 vs. 0.27 ± 0.015 mg/100 g; p < 0.05), whereas in group C exhibited a significant decrease over time. Fat, SFA, UFA, MUFA, and PUFA levels were significantly elevated in group D relative to group C ( p < 0.05), while SCC showed a significant reduction in the treated group than the control one (104.4 ± 20.12 vs. 136.6 ± 32.24 × 10³ cells/mL; p < 0.05). No significant differences were observed in pregnancy rates; however, the calving-conception interval was significantly shortened in group D (62.23 ± 6.17 vs. 72.88 ± 5.49 days; p < 0.01). The obtained results indicate that the parenteral administration of the vitamin combination was associated with changes in selected milk quality parameters and with a shorter calving-conception interval.

Comparative life cycle assessment of paper and cardboard based packaging solutions for e-commerce: A case study on a book application - Maria Vittoria Rizzo; Giuseppe Vignali (Science of The Total Environment, 2026)

Impact of glacial meltwater on prokaryotic dynamics in high Arctic fjords - Angelina Lo Giudice; Carmen Rizzo; Maria Papale; Alessandro Ciro Rappazzo (Frontiers in Marine Science, 2026)
Arctic fjords are among the most sensitive ecosystems, particularly affected by rapid cryospheric changes. One of the most prominent consequences of global warming in these regions is the increasing input of glacial meltwater, which alters the physical and chemical structure of fjord systems and profoundly affects prokaryotic (bacterial and archaeal) communities. Despite these changes, the impacts on prokaryotic communities, central players in biogeochemical cycles and ecosystem functioning, remain poorly understood. This review synthesizes current knowledge on how glacial meltwater influences prokaryotic dynamics in Arctic fjords pelagic ecosystems, with a focus on community composition, functional potential, and biogeochemical implications. We explore how freshwater influx affects salinity, turbidity, nutrient fluxes, and organic matter availability drives prokaryotic selection processes. Critical knowledge gaps remain, particularly in linking taxonomic shifts to changing ecosystem dynamics and predicting long-term ecological trajectories under the continued intensification of meltwater input. We emphasize the urgent need for integrative, multi-seasonal studies combining molecular tools, biogeochemical measurements, and modeling approaches to fully understand prokaryotic responses to ongoing environmental change in Arctic fjords.

Diversity and ecology of the prokaryotic microbiome associated with marine sponges across Antarctica - Angelina Lo Giudice; Maria Papale; Marco Bertolino; Anna Reboa; Carmen Rizzo (Science of The Total Environment, 2026)

Intrauterine oxygen/ozone mixture for the treatment of subclinical endometritis in repeat breeder cows - Alice Carbonari; Matteo Burgio; Lorenza Frattina; Vincenzo Cicirelli; Fabrizio Iarussi; Maria Tempesta; Maria Stella Lucente; Annalisa Rizzo; Grazia Greco (Research in Veterinary Science, 2026)

Bacterial community and chemical contamination in high-latitude lake waters: a comparative study from the Svalbard and Antarctic Peninsula regions - Alessandro Ciro Rappazzo; Angelina Lo Giudice; Carmen Rizzo; Stefania Giannarelli; Lisa Ghezzi; Maurizio Azzaro; Warren Raymond Lee Cairns; Maria Papale (Environmental Research, 2026)

Novel sustainable strategies to mitigate toxicity of emerging contaminants: cellular and physiological insights from CMIT-exposed mussels treated with insect-based protein hydrolysates - Cristiana Roberta Multisanti; Kristian Riolo; Maria Giovanna Rizzo; Federica Impellitteri; Giuseppe Piccione; Monia Perugini; Alessia Giannetto; Caterina Faggio (Sustainable Chemistry and Pharmacy, 2025)

Photoactivity of Pluronic® F-127 nanoencapsulated hypericin against Leishmania: A promising approach for cutaneous leishmaniasis - Larissa Ferreira de Oliveira; Alanis Boer dos Reis; Ana Paula Rizzo Bueno; Tiffany Suzawa; Maria Julia Schiavon Gonçalves; Anibal Salinas Junior; Ana Carolina Vieira de Oliveira; Paulo Cesar Souza Pereira; Wilker Caetano; Flavio Augusto Vicente Seixas; Áquila Carolina Fernandes Herculano Ramos-Milaré; Daniele Stefanie Sara Lopes Lera-Nonose; et al. (Journal of Photochemistry and Photobiology B: Biology, 2025)

Dynamic changes in plasma electrophoretic protein profiles of different goat breeds during peripartum: implications for immuno-inflammatory monitoring - Stella Agradi; Alda Quattrone; Giulio Curone; Gabriele Brecchia; Federica Arrigo; Alessandro Zumbo; Giuseppe Piccione; Maria Rizzo; Francesca Arfuso (Veterinary Research Communications, 2025)

First Record of Sepioteuthis lessoniana from the Maltese Archipelago, with Further Notes on Its Occurrence in the Central Mediterranean Sea - Alessio Marrone; Alan Deidun; Maria Corsini-Foka; Bruno Zava; Eleonora Tinto; Carmen Rizzo; Pietro Battaglia (Journal of Marine Science and Engineering, 2025)
The occurrence of the bigfin reef squid Sepioteuthis lessoniana, a Lessepsian migrant, is documented for the first time from the coastal waters off Malta, based on the collection of a single specimen reported through citizen science. The presence of this species in the broader Strait of Sicily region is further confirmed by a morphometric assessment and genetic analysis of another individual captured off the Pelagian island of Lampedusa. Molecular identification using mitochondrial COI and 16S rRNA markers corroborates the taxonomic identification exercise as it aligns both specimens with Indo-Pacific clades of S. lessoniana. These records represent the first genetically verified occurrences of the species in both Maltese and Italian waters. The findings extend the known Mediterranean distribution of S. lessoniana, emphasizing the Strait of Sicily as an important monitoring region for Lessepsian migrants and highlighting the combined role of integrative taxonomy and citizen science in tracking non-indigenous species introductions.

PCB-oxidizing bacteria in Arctic and Antarctic lakes: insights into bioremediation potential in polar ecosystems - Alessandro Ciro Rappazzo; Carmen Rizzo; Stefania Giannarelli; Marco Vecchiato; Angelina Lo Giudice; Maurizio Azzaro; Maria Papale (Polar Biology, 2025)
Polychlorinated biphenyls (PCBs) are long-lasting organic pollutants commonly found in polar regions due to their ability to be transported and deposited over long distances in the atmosphere. This study examined the levels of PCB contamination in water and sediment samples taken from Arctic lakes (Ny-Ålesund, Svalbard) and Antarctic lakes (Livingston Island and Deception Island) and evaluated the biodegradation capabilities of local cold-adapted bacteria. Our analyses highlighted that Antarctic lakes had higher PCB concentrations than Arctic lakes, and the sediments acted as sinks for these pollutants. Variability between lakes was also observed, with Deception Island exhibiting higher PCB levels, which may be attributed to local environmental and volcanic influences. Several bacterial strains able to grow with PCBs as the sole carbon and energy source were isolated and identified from sediment samples, primarily belonging to the genus Pseudomonas . Arctic isolates exhibited higher biodegradation efficiency, particularly those possessing the bphA gene, which plays a key role in the initial steps of PCB degradation. These preliminary results underscore the essential role of polar lakes as both reservoirs and key areas for PCB degradation, while also highlighting the potential of cold-adapted bacteria for bioremediation in extreme environments.

First study on microbial community-level physiological profiles across a subArctic Atlantic marine transect - Gabriella Caruso; Giovanna Maimone; Alessandro Ciro Rappazzo; Maria Papale; Carmen Rizzo; Alessandro Cosenza; Angelina Lo Giudice; Maurizio Azzaro (Polar Biology, 2025)
In SubArctic ecosystems, the microbial metabolic response to environmental changes is still underinvestigated. In the framework of the pan-Arctic Synoptic Arctic Survey network, the microbial community physiological profiles were determined by Biolog Ecoplates in a pelagic transect crossing the Greenland Sea at 75°N. At six hydrographic stations, seawater was sampled to cover the whole water column ranging from surface to 3532 m of depth. Spatially different metabolic pathways were found, with carbohydrates, carboxylic acids and amino acids preferentially metabolized within the photic zone (mean value 22.5, 22.3 and 18% of the total, respectively), carbohydrates and carboxylic acids in the aphotic zone (26.40 and 24.17%, respectively. High-carbon substrate utilization rates were recorded in the middle of the transect. Community-level physiological profiles were not affected by abiotic parameters, except in the aphotic zone, where carbohydrate and carboxylic acid utilization correlated with temperature. Being the first dataset available in this subArctic area, the observed metabolic patterns hold remarkable ecological interest also in the light of future global warming scenarios, underlining the microbial physiological plasticity to utilize a diversified range of organic substrates in such an extremely dynamic environment.

Morphological traits of prokaryoplankton across an Atlantic subarctic marine transect - Giovanna Maimone; Angelina Lo Giudice; Maria Papale; Alessandro Ciro Rappazzo; Carmen Rizzo; Alessandro Cosenza; Rodolfo Paranhos; Anderson de Souza Cabral; Federica Relitti; Martina Kralj; Maurizio Azzaro (Polar Biology, 2025)

Environmental factors influence goat immune response to PFOS and glyphosate: Difference between grazing and stall-feeding - Francesco Molinari; Gianluca Antonio Franco; Francesca Inferrera; Nicla Tranchida; Antonella Iaconis; Maria Rizzo; Davide Di Paola; Giuseppe Piccione; Enrico Gugliandolo (Environmental Toxicology and Pharmacology, 2025)

Changes in plasma UCP-1, leptin, lipids, and pro-inflammatory interleukins in calves from birth to weaning - Francesca Arfuso; Federica Arrigo; Vincenzo Lopreiato; Maria Rizzo; Luigi Liotta; Claudia Giannetto; Giuseppe Piccione (Research in Veterinary Science, 2025)

Microbiome and pollutants in the freshwater sponges Ephydatia muelleri (Lieberkühn, 1856) and Spongilla lacustris (Linnaeus, 1758) from the sub-Arctic Pasvik river (Northern Fennoscandia) - Carmen Rizzo; Gabriella Caruso; Giovanna Maimone; Luisa Patrolecco; Marco Termine; Marco Bertolino; Stefania Giannarelli; Alessandro Ciro Rappazzo; Josef Elster; Alessio Lena; Maria Papale; Tanita Pescatore; et al. (Environmental Research, 2025)

The helium and carbon isotopic signature of Ocean island basalts: Insights from Fogo volcano (Cape Verde archipelago) - Francesco Maria Lo Forte; Guillaume Boudoire; Maria Luce Frezzotti; Silvio Giuseppe Rotolo; Andres Sandoval-Velasquez; Fátima Viveiros; Vittorio Zanon; Alessandro Aiuppa; Andrea Luca Rizzo (Earth and Planetary Science Letters, 2024)

Urban wastewater disinfection by FeCl3-activated biochar/peroxymonosulfate system: Escherichia coli inactivation and microplastics interference - Mister Adeel; Claudia Cirillo; Maria Sarno; Luigi Rizzo (Environmental Pollution, 2024)

Monitoring the physiological inflammatory alertness in horse after road transport - Federica Arrigo; Francesca Aragona; Caterina Faggio; Elisabetta Giudice; Claudia Giannetto; Giuseppe Piccione; Maria Rizzo; Francesca Arfuso (Veterinary Research Communications, 2024)

Structural properties and microbial diversity of the biofilm colonizing plastic substrates in Terra Nova Bay (Antarctica) - Maria Papale; Stefano Fazi; Maila Severini; Roberta Scarinci; Ombretta Dell'Acqua; Maurizio Azzaro; Valentina Venuti; Barbara Fazio; Enza Fazio; Vincenza Crupi; Alessia Irrera; Carmen Rizzo; et al. (Science of The Total Environment, 2024)

First observations on airborne prokaryotes in a subArctic Atlantic marine area - Maurizio Azzaro; Carmen Rizzo; Giovanna Maimone; Maria Papale; Alessandro Ciro Rappazzo; Angelina Lo Giudice; Alessandro Cosenza; Matteo Feltracco; Maya Petricciuolo; Ermanno Federici; Vito Vitale (Polar Science, 2024)

Welfare and stress assessment of tourism carriage horses under real working conditions in Sicily - Francesca Arfuso; Maria Rizzo; Federica Arrigo; Francesco Francaviglia; Laura Perillo; Pietro Schembri; Luigi Emiliano Maria Zumbo; Rosaria Disclafani; Giuseppe Piccione; Vincenzo Monteverde (Journal of Equine Veterinary Science, 2024)

Multi-elemental analysis of commercial wheat flours by ICP-MS triple quadrupole in function of the milling degree - Chiara Telloli; Flavio Cicconi; Emanuele Manzi; Fabio Borgognoni; Stefano Salvi; Maria Carmela Iapalucci; Antonietta Rizzo (Food Chemistry, 2024)

Prokaryotic diversity in the sponges Mycale (Oxymycale) acerata (Kirkpatrick, 1907) and Dendrilla antarctica (Topsent, 1905) from two distant Antarctic marine areas: South Cove at Rothera Point (Adelaide Island, Western Antarctic Peninsula) and Thetys Bay (Terra Nova Bay, Ross Sea) - Angelina Lo Giudice; Maria Papale; Maurizio Azzaro; Carmen Rizzo (Deep Sea Research Part II: Topical Studies in Oceanography, 2024)

Using infrared thermography for the evaluation of road transport thermal homeostasis in athletic horse - Francesca Aragona; Francesca Arfuso; Maria Rizzo; Francesco Fazio; Giuseppe Acri; Giuseppe Piccione; Claudia Giannetto (Journal of Equine Veterinary Science, 2024)

Carbon and nitrogen, humic and labile fractions in soil under clonal eucalyptus stands from cerrado - Wendel dos Santos Moraes; Luiz Fernandes Silva Dionisio; Gustavo Schwartz; Juliana Andrade Pereira; Jossimara Ferreira Damascena; Felipe Alexandre Rizzo; Alberto Bentes Brasil Neto; Camila de Almeida Milhomem; José Maria Arcanjo Alves; Renisson Neponuceno Araujo Filho; Renato de Almeida Sarmento; Alinne da Silva; et al. (European Journal of Forest Research, 2024)

Assessing climate change vulnerability of coastal roads - Lucia Rocchi; Anthony G. Rizzo; Luisa Paolotti; Antonio Boggia; Maria Attard (Mitigation and Adaptation Strategies for Global Change, 2024)
Climate change is a global phenomenon, which affects in several ways different regions all around the world, beyond the rise in global temperature. Among the different climate change issues, the management of transport infrastructures is crucial. Particularly, their vulnerability against changes in climatic conditions should be assessed. Vulnerability indicators are based on the IPCC concept of vulnerability and can be defined as a function of Climate Exposure, Sensitivity, and Adaptive Capacity. These dimensions need to be addressed during the assessment making and can be modelled as a Multiple Criteria Decision Analysis (MCDA) problem. This study proposes an integrated approach of several MCDA methods as a possible tool for ranking the climate change vulnerability of coastal roads in Malta. The application covers six coastal roads in the islands of Malta, classified by three different MCDA methods. The results indicate that the proposed approach can produce a consistent ranking of the climate change vulnerability of coastal roads. The study provides policy and decision-makers with a definition of a coastal road, an inventory of such roads, a list of climate change impacts, and a mathematical model incorporating climate change vulnerability indicators. The model can be used to prioritize investment and plan climate change adaptation strategies for infrastructural works on coastal roads.

Rhythmicity of locomotor behavior and body temperature in Felis catus maintained under controlled microclimate conditions - Raúl Delmar Cerutti; Maria Rizzo; Andrea Bonomo; Claudia Giannetto; María Cristina Scaglione; Giuseppe Piccione (Journal of Veterinary Behavior, 2024)

Correction to: Matrix metalloproteinase-2 (MMP-2) generates soluble HLA-G1 by cell surface proteolytic shedding - Roberta Rizzo; Alessandro Trentini; Daria Bortolotti; Maria C. Manfrinato; Antonella Rotola; Massimiliano Castellazzi; Loredana Melchiorri; Dario Di Luca; Franco Dallocchio; Enrico Fainardi; Tiziana Bellini (Molecular and Cellular Biochemistry, 2024)

Detection and typization of HPV genotypes in subjects with oral and upper respiratory tract lesions, Milan, Italy - Alberto Rizzo; Federica Salari; Angelo Eplite; Andrea Giacomelli; Davide Moschese; Davide Dalu; Maria Vittoria Cossu; Rosaria Lorusso; Giacomo Pozza; Loriana Morelli; Cinzia Fasola; Claudia Tonielli; et al. (Infectious Diseases, 2024)

Application of an integrated pyrolysis and chemical leaching process for pulper waste conversion into coal, hydrogen and chemical flocculating agent - Andrea Salimbeni; Marta Di Bianca; Andrea Maria Rizzo; David Chiaramonti (Waste Management, 2024)

Serum from COVID-19 patients promotes endothelial cell dysfunction through protease-activated receptor 2 - Francesco Vieceli Dalla Sega; Francesca Fortini; Danilo Licastro; Simeone Dal Monego; Margherita Degasperi; Alessia Ascierto; Luisa Marracino; Paolo Severi; Maria D’Accolti; Irene Soffritti; Marta Brambilla; Marina Camera; et al. (Inflammation Research, 2024)

Progressive Ataxia and Palatal Tremor Is Not Associated with IgLON5 Antibodies: Results From Two Cases - Andrea Mastrangelo; Maria Pia Giannoccaro; Vincenzo Donadio; Fortuna Ricciardiello; Felice Di Laudo; Flavia Palombo; Rocco Liguori; Giovanni Rizzo (The Cerebellum, 2023)

Marine sponges as bioindicators of pollution by synthetic microfibers in Antarctica - Andrea Corti; Giulia Pagano; Angelina Lo Giudice; Maria Papale; Carmen Rizzo; Maurizio Azzaro; Virginia Vinciguerra; Valter Castelvetro; Stefania Giannarelli (Science of The Total Environment, 2023)

Remote sensing of the Earth's soil color in space and time - Rodnei Rizzo; Alexandre M.J.-C. Wadoux; José A.M. Demattê; Budiman Minasny; Vidal Barrón; Eyal Ben-Dor; Nicolas Francos; Igor Savin; Raul Poppiel; Nelida E.Q. Silvero; Fabrício da Silva Terra; Nícolas Augusto Rosin; et al. (Remote Sensing of Environment, 2023)

Sponges (Porifera) from the Ross Sea (Southern Ocean) with taxonomic and molecular re-description of two uncommon species - Gabriele Costa; Angelina Lo Giudice; Maria Papale; Carmen Rizzo; Maurizio Azzaro; Alice Guzzi; Marco Grillo; Marco Bertolino (Polar Biology, 2023)

Screening of Undaria pinnatifida (Laminariales, Phaeophyceae) Lipidic Extract as a New Potential Source of Antibacterial and Antioxidant Compounds - Loredana Stabili; Maria Immacolata Acquaviva; Ester Cecere; Carmela Gerardi; Antonella Petrocelli; Francesco Paolo Fanizzi; Federica Angilè; Lucia Rizzo (Journal of Marine Science and Engineering, 2023)
The lipidic extract of Undaria pinnatifida, one of the worst invasive species, was investigated for its potential exploitation in biotechnological applications. The antimicrobial activity of the lipidic extract in three different portions (blade, sporophyll, and holdfast) was assessed by using the Kirby–Bauer method, while the antioxidant activity was evaluated by the TEAC, ORAC, and Folin–Ciocalteu assays. NMR spectroscopy and thin-layer chromatography were employed for the chemical characterization. The extracts showed antibacterial activity against several of the tested Vibrio species: V. aestuarinus, V. fischeri, V. furnisii, V. inusitatus, V. litoralis, and V. mediterranei, including some pathogens for farmed fish. Intriguing antioxidant activity was recorded, with the highest value in the blade (126.907 ± 28.993 mmol Trolox equivalent/g TEAC). Free, saturated, unsaturated, and polyunsaturated fatty acids were highlighted by 1D and 2D NMR spectroscopy. The presence of ω-3 and ω-6 PUFAs indicates the importance of this algal species in the food industry. We suggest the employment of U. pinnatifida as source of new and safer therapeutic agents to control fish and shellfish diseases due to vibriosis, as well as a source of natural antioxidants that are useful for human health, considering the growing interest in the development of strategies for invasive seaweed control.

Biochemical composition and reproductive cycle of the clam Chamelea gallina in the Northern Adriatic Sea: an after-10-year comparison of patterns and changes - Vanessa Moschino; Giulia Rizzo; Tihana Marĉeta; Federica Cernigai; Luciano Masiero; Luisa Da Ros; Maria Gabriella Marin (Frontiers in Marine Science, 2023)
The study of the relationships between growth patterns, energy reserves and reproduction, and their interdependency with environmental variables is crucial to increase the knowledge of the physiological processes regulating the recruitment and survival of commercially exploited bivalve species. In the present study, the biochemical profile and gametogenic cycle of the striped Venus clam Chamelea gallina monthly sampled in fishing grounds of the Chioggia district in 2001 and 2010 were investigated to identify possible variations that occurred after 10 years and to analyze inter-relationships among the biological parameters with changing environmental conditions. Our results indicated that higher phytoplankton availability and increased water temperature recorded from 2001 to 2010 resulted in higher reserve accumulation, mostly in the form of proteins, carbohydrates and glycogen. An increase was also observed in the calcification rate of the shells, which consequently became heavier in clams collected in 2010. Moreover, in 2010, as for the reproductive conditions, a prolonged spawning period was observed with respect to 2002. Overall results highlighted clear-cut differences in the physiological performances of clams collected in 2001 and 2010, suggesting the importance to monitor changes over time to unveil potential pros and cons for single populations of commercial interest.

Factors associated with small ruminant lentivirus infection in goat herds from Pernambuco state, Northeast region of Brazil - José Andreey Almeida Teles; Sérgio Alves Nascimento; Elialdo Xavier Melo; Erivânia Camelo Almeida; Maria Fernanda Vianna Marvulo; Huber Rizzo; Denise Batista Nogueira; Sérgio Santos de Azevedo; Jean Carlos Ramos Silva; Roberto Soares Castro (Preventive Veterinary Medicine, 2023)

Conceptual design and techno-economic assessment of coupled hydrothermal liquefaction and aqueous phase reforming of lignocellulosic residues - Edoardo Tito; Giulia Zoppi; Giuseppe Pipitone; Edoardo Miliotti; Arturo Di Fraia; Andrea Maria Rizzo; Raffaele Pirone; David Chiaramonti; Samir Bensaid (Journal of Environmental Chemical Engineering, 2023)

Immune and Inflammatory Response of Donkeys (Equus asinus) Tested Positive to Tick-borne Pathogens - Raffaella Cocco; Maria Rizzo; Carlo Carta; Francesca Arfuso; Giuseppe Piccione; Sebastiano Luridiana; Alberto Crovace; Eraldo Sanna Passino; Sara Sechi (Journal of Equine Veterinary Science, 2023)

Exposure to acetaminophen impairs gametogenesis and fertility in zebrafish (Danio rerio) - Davidson Peruci Moreira; Yves Moreira Ribeiro; Camila Stephanie Ferreira; Samyra Maria dos Santos Nassif Lacerda; Elizete Rizzo (Archives of Toxicology, 2023)

Designation of optimal reference strains representing the infant gut bifidobacterial species through a comprehensive multi‐omics approach - Federico Fontana; Giulia Alessandri; Chiara Tarracchini; Massimiliano Giovanni Bianchi; Sonia Mirjam Rizzo; Leonardo Mancabelli; Gabriele Andrea Lugli; Chiara Argentini; Laura Maria Vergna; Rosaria Anzalone; Giulia Longhi; Alice Viappiani; et al. (Environmental Microbiology, 2022)
The genomic era has resulted in the generation of a massive amount of genetic data concerning the genomic diversity of bacterial taxa. As a result, the microbiological community is increasingly looking for ways to define reference bacterial strains to perform experiments that are representative of the entire bacterial species. Despite this, there is currently no established approach allowing a reliable identification of reference strains based on a comprehensive genomic, ecological, and functional context. In the current study, we developed a comprehensive multi‐omics approach that will allow the identification of the optimal reference strains using the Bifidobacterium genus as test case. Strain tracking analysis based on 1664 shotgun metagenomics datasets of healthy infant faecal samples were employed to identify bifidobacterial strains suitable for in silico and in vitro analyses. Subsequently, an ad hoc bioinformatic tool was developed to screen local strain collections for the most suitable species‐representative strain alternative. The here presented approach was validated using in vitro trials followed by metagenomics and metatranscriptomics analyses. Altogether, these results demonstrated the validity of the proposed model for reference strain selection, thus allowing improved in silico and in vitro investigations both in terms of cross‐laboratory reproducibility and relevance of research findings.

Idiomarina sp. Isolates from Cold and Temperate Environments as Biosurfactant Producers - Carmen Rizzo; Maria Papale; Angelina Lo Giudice (Journal of Marine Science and Engineering, 2022)
Background: The cold-adapted Idiomarina sp. 185 from Antarctic shoreline sediment and the mesophilic Idiomarina sp. A19 from the brackish Lake Faro (Italy) were screened for their efficiency in biosurfactant production by a temperature-mediated approach, when grown in rich culture medium and mineral medium supplemented with biphenyl. Methods: oxidation of polychlorobiphenyls and standard screening tests were performed, i.e., E24 index detection, surface tension measurement, blood agar plate and C-TAB agar plate. Results: During incubation in rich medium, the strain Idiomarina sp. A19 produced an excellent stable emulsion, recording an E24 of 73.5%. During growth in mineral medium, isolates showed good efficiency in at least one performed condition by showing species-specific differences related to optimum temperature. In the presence of biphenyl, both Idiomarina isolates created stable emulsions (E24 ≈ 47.5 and 35%, respectively), as well as surface tension reductions of 30.05 and 35.5 mN/m, respectively. Further differences between isolates were observed by phenotypic characterization. The genome mining approach on available deposited genome sequences for closest relatives offered further insights about the presence of genes for biphenyl degradation, especially for microorganisms derived from different extreme environments. Conclusions: Our results allowed for an interesting comparison which underlined differences in metabolic patterns and in the kinetics of BS production, probably due to the different origins of the strains.

Isolation and Identification of Luminescent Bacteria in Deep Sea Marine Organisms from Sicilian Waters (Mediterranean Sea) - Rosario Calogero; Carmen Rizzo; Erika Arcadi; Maria Giulia Stipa; Pierpaolo Consoli; Teresa Romeo; Pietro Battaglia (Journal of Marine Science and Engineering, 2022)
Luminescent bacteria are a fascinating component of marine microbial communities, often related to the light emissions in deep sea marine organisms. They are mainly affiliated with specific phylogenetic groups, such as Photobacterium, Vibrio, and Photorhabdus, and are sometimes involved in symbiotic relationships. However, the luminescence of some marine organisms remains a poorly understood process, and it is not always certain whether their luminescence is attributable to associated luminescent bacteria. In this study, for the first time, luminescent bacteria were isolated from two deep sea organisms, namely, the cephalopod Neorossia caroli and the teleost Chlorophthalmus agassizi. The isolation was carried out on glycerol-supplemented medium, and the search for the luxAB gene was performed on all isolates as a complementary tool to the culture-dependent techniques to detect bioluminescence by molecular approach. The optimum of salinity, temperature, and pH was evaluated by physiological tests for all isolates. The production of extracellular polymeric substances was also preliminarily screened. A total of 24 luminescent isolates were obtained, with an abundance from C. agassizi specimens. All the isolates were taxonomically characterized and were related to different species of Photobacterium, with the exception of Vibrio sp. CLD11 that was from C. agassizi. The luxAB gene was detected in about the 90% of the analysed strains.

Antarctic Porifera homogenates as a source of enzymes and antibacterial substances: first results - Gabriella Caruso; Maria Papale; Maurizio Azzaro; Carmen Rizzo; Pasqualina Laganà; Rosalba Caruso; Angelina Lo Giudice (Polar Biology, 2022)
Marine Porifera (sponges) are known to produce several bioactive metabolites having a biotechnological potential, mostly derived from their bacterial symbionts; however, current knowledge on the production of metabolites such as enzymes and antibacterial molecules in sponges living in Antarctic environments is not fully exhaustive and needs further deepened investigation. The interest in discovering the broad spectrum of natural products potentially derived from species adapted to colonize extreme environments stimulates the research toward Antarctic sponge bioprospection. In this study, whole homogenates of Antarctic Demospongiae, belonging to five different species [ Haliclona ( Rhizoniera ) sp., Haliclona ( Rhizoniera ) dancoi, Microxina sarai, Dendrilla antarctica, and Mycale acerata ] were collected from Terra Nova Bay (Ross Sea) and examined for presence and activity of enzymes, including lysozyme, and antibacterial substances. Enzyme activities (leucine aminopeptidase, beta-glucosidase, and alkaline phosphatase) were measured using fluorogenic substrates; lysozyme content was determined on plates containing lyophilized Micrococcus lysodeikticus cell walls as a substrate. Homogenates were screened in microtiter plates for their antibacterial activity against Antarctic bacterial isolates, and the absorbance reduction was measured with a microplate reader. All homogenates exhibited proteolytic, glycolytic, and phosphatasic activities, lysozyme and antibacterial activities at near “in situ” temperature (5 °C), with some differences among the examined species. Results confirmed that Antarctic sponge homogenates are interesting sources of different bioactive substances, likely produced from associated bacterial symbionts, and that could have great potential to be used in medicine or industrial applications.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Melaleuca alternifolia essential oil soap: a potential alternative for hand hygiene - Juliana Rizzo Gnatta; Vanessa de Brito Poveda; Maria Clara Padoveze; Kazuko Uchikawa Graziano; Ruth Natalia Teresa Turrini; Maria Júlia Paes da Silva (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Improving the computational efficiency of first arrival time uncertainty estimation using a connectivity-based ranking Monte Carlo method - Maria Morvillo; Alessandra Bonazzi; Calogero B. Rizzo; Felipe P. J. de Barros (Stochastic Environmental Research and Risk Assessment, 2021)

Antibiofilm Activity of Antarctic Sponge-Associated Bacteria against Pseudomonas aeruginosa and Staphylococcus aureus - Carmen Rizzo; Vincenzo Zammuto; Angelina Lo Giudice; Maria Giovanna Rizzo; Antonio Spanò; Pasqualina Laganà; Miguel Martinez; Salvatore Guglielmino; Concetta Gugliandolo (Journal of Marine Science and Engineering, 2021)
Bioprospecting in unusual marine environments provides an innovative approach to search novel biomolecules with antibiofilm activity. Antarctic sponge-associated bacteria belonging to Colwellia, Pseudoalteromonas, Shewanella and Winogradskyella genera were evaluated for their ability to contrast the biofilm formation by Pseudomonas aeruginosa ATCC 27853 and Staphylococcus aureus ATCC 29213, as model organisms. All strains were able to produce biofilm at both 4 and 25 °C, with the highest production being for Colwellia, Shewanella and Winogradskyella strains at 4 °C after 24 h. Antibiofilm activity of cell-free supernatants (CFSs) differed among strains and on the basis of their incubation temperature (CFSs4°C and CFSs25°C). The major activity was observed by CFSs4°C against S. aureus and CFSs25°C against P. aeruginosa, without demonstrating a bactericidal effect on their growth. Furthermore, the antibiofilm activity of crude extracts from Colwellia sp. GW185, Shewanella sp. CAL606, and Winogradskyella sp. CAL396 was also evaluated and visualized by confocal laser scanning microscopic images. Results based on the surface-coating assay and surface tension measurements suggest that CFSs and the crude extracts may act as biosurfactants inhibiting the first adhesion of P. aeruginosa and S. aureus. The CFSs and the novel biopolymers may be useful in applicative perspectives for pharmaceutical and environmental purposes.

Divergent minute virus of canines strains identified in illegally imported puppies in Italy - M. Campalto; M. Carrino; L. Tassoni; G. Rizzo; M. C. Rossmann; M. Cocchi; P. De Benedictis; Maria Serena Beato (Archives of Virology, 2020)
Minute virus of canines (MVC) belongs to the family Parvoviridae , genus Bocaparvovirus , and has been mainly described during enteritis episodes in young dogs. This study reports the characterization of four divergent MVC strains detected between 2012 and 2018, three of which were from dogs illegally imported into Italy, most probably from Eastern Europe, that cluster together phylogenetically but share low genetic similarity with the fourth MVC from an autochthonous dog and other available MVC sequences. Our data indicate that the introduction of genetically distinct MVC strains occurred through the illegal movement of dogs from a geographic area where a distinct MVC lineage was most likely circulating. Enforced surveillance of MVC in the dog population of Eastern Europe and its neighboring countries may shed light on, and eventually trace back to, illegal animal movements.

Land use changes in Southeastern Amazon and trends in rainfall and water yield of the Xingu River during 1976–2015 - Rodnei Rizzo; Andrea S. Garcia; Vívian M. de F. N. Vilela; Maria Victoria R. Ballester; Christopher Neill; Daniel C. Victoria; Humberto R. da Rocha; Michael T. Coe (Climatic Change, 2020)

Adalimumab effectively controls both anterior and posterior noninfectious uveitis associated with systemic inflammatory diseases: focus on Behçet’s syndrome - Elena Silvestri; Alice Bitossi; Alessandra Bettiol; Giacomo Emmi; Maria Letizia Urban; Irene Mattioli; Gerardo Di Scala; Daniela Bacherini; Giuseppe Lopalco; Vincenzo Venerito; Florenzo Iannone; Antonio Vitale; et al. (Inflammopharmacology, 2020)

Modeling Macroalgal Forest Distribution at Mediterranean Scale: Present Status, Drivers of Changes and Insights for Conservation and Management - Erika Fabbrizzi; Michele Scardi; Enric Ballesteros; Lisandro Benedetti-Cecchi; Emma Cebrian; Giulia Ceccherelli; Francesco De Leo; Alan Deidun; Giuseppe Guarnieri; Annalisa Falace; Silvia Fraissinet; Chiara Giommi; et al. (Frontiers in Marine Science, 2020)

miR-143 expression profiles in urinary bladder cancer: correlation with clinical and epidemiological parameters - Nouha Setti Boubaker; Manuela Spagnuolo; Nesrine Trabelsi; Rahma Said; Aymone Gurtner; Giulia Regazzo; Haroun Ayed; Ahlem Blel; Omar Karray; Ahmed Saadi; Soumaya Rammeh; Mohamed Chebil; et al. (Molecular Biology Reports, 2020)

Metals/Metalloids and Oxidative Status Markers in Saltwater Fish from the Ionic Coast of Sicily, Mediterranean Sea - Chiara Copat; Milena Rizzo; Agata Zuccaro; Alfina Grasso; Pietro Zuccarello; Maria Fiore; Giuseppe Mancini; Margherita Ferrante (International Journal of Environmental Research, 2020)

Characterizing Small Private Forests and Forest Owners’ Motivations and Attitudes in Trentino (Eastern Alps, Italy) - Maria Rizzo; Patrizia Gasparini; Sergio Tonolli; Roberto Zoanetti; Dino Buffoni; Francesco Dellagiacoma (Small-scale Forestry, 2019)

Bacterial communities versus anthropogenic disturbances in the Antarctic coastal marine environment - Angelina Lo Giudice; Gabriella Caruso; Carmen Rizzo; Maria Papale; Maurizio Azzaro (Environmental Sustainability, 2019)

A new variant of Xylella fastidiosa subspecies multiplex detected in different host plants in the recently emerged outbreak in the region of Tuscany, Italy - Maria Saponari; Giusy D’Attoma; Raied Abou Kubaa; Giuliana Loconsole; Giuseppe Altamura; Stefania Zicca; Domenico Rizzo; Donato Boscia (European Journal of Plant Pathology, 2019)

Metal Resistance in Bacteria from Contaminated Arctic Sediment is Driven by Metal Local Inputs - Simona Caputo; Maria Papale; Carmen Rizzo; Stefania Giannarelli; Antonella Conte; Federica Moscheo; Marco Graziano; Paul Eric Aspholm; Massimo Onor; Emilio De Domenico; Stefano Miserocchi; Luigi Michaud; et al. (Archives of Environmental Contamination and Toxicology, 2019)

Groundwater characterization from an ecological and human perspective: an interdisciplinary approach in the Functional Urban Area of Parma, Italy - Andrea Zanini; Emma Petrella; Anna Maria Sanangelantoni; Letizia Angelo; Beatrice Ventosi; Luca Viani; Pietro Rizzo; Sara Remelli; Marco Bartoli; Rossano Bolpagni; Alessandro Chelli; Alessandra Feo; et al. (Rendiconti Lincei. Scienze Fisiche e Naturali, 2019)

Combining phylogeography and future climate change for conservation of Bombus morio and B. pauloensis (Hymenoptera: Apidae) - Elaine Françoso; Alexandre Rizzo Zuntini; Maria Cristina Arias (Journal of Insect Conservation, 2019)

Idiopathic hypertrophic pachymeningitis: an autoimmune IgG4-related disease - Armando De Virgilio; Marco de Vincentiis; Maurizio Inghilleri; Giovanni Fabrini; Michela Conte; Andrea Gallo; Maria Ida Rizzo; Antonio Greco (Immunologic Research, 2017)

Glaucoma: recent advances in the involvement of autoimmunity - Maria Ida Rizzo; Antonio Greco; Armando De Virgilio; Andrea Gallo; Luciano Taverniti; Massimo Fusconi; Michela Conte; Giulio Pagliuca; Rosaria Turchetta; Marco de Vincentiis (Immunologic Research, 2017)

Indoleamine-2,3-Dioxygenase/Kynurenine Pathway as a Potential Pharmacological Target to Treat Depression Associated with Diabetes - Isabella Caroline da Silva Dias; Bruno Carabelli; Daniela Kaori Ishii; Helen de Morais; Milene Cristina de Carvalho; Luiz E. Rizzo de Souza; Silvio M. Zanata; Marcus Lira Brandão; Thiago Mattar Cunha; Anete Curte Ferraz; Joice Maria Cunha; Janaina Menezes Zanoveli (Molecular Neurobiology, 2016)

Telomeres and telomerase in head and neck squamous cell carcinoma: from pathogenesis to clinical implications - Paolo Boscolo-Rizzo; Maria Cristina Da Mosto; Enrica Rampazzo; Silvia Giunco; Annarosa Del Mistro; Anna Menegaldo; Lorena Baboci; Monica Mantovani; Giancarlo Tirelli; Anita De Rossi (Cancer and Metastasis Reviews, 2016)

Targeting cellular and molecular drivers of head and neck squamous cell carcinoma: current options and emerging perspectives - Simonetta Ausoni; Paolo Boscolo-Rizzo; Bhuvanesh Singh; Maria Cristina Da Mosto; Giacomo Spinato; Giancarlo Tirelli; Roberto Spinato; Giuseppe Azzarello (Cancer and Metastasis Reviews, 2016)

Therapeutic drug monitoring of second-generation antipsychotics in pediatric patients: an observational study in real-life settings - Marco Pozzi; Dario Cattaneo; Sara Baldelli; Serena Fucile; Annalisa Capuano; Carmela Bravaccio; Liberata Sportiello; Silvana Bertella; Fabiana Auricchio; Renato Bernardini; Carmen Ferrajolo; Giuseppe Guastella; et al. (European Journal of Clinical Pharmacology, 2016)

Risk assessment of non-target effects of Closterocerus chamaeleon (Girault) parasitoid of the eucalypt gall maker Ophelimus maskelli (Ashmead) (Hymenoptera, Eulophidae) - Maria Concetta Rizzo; Gabriella Lo Verde; Roberto Rizzo; Virgilio Caleca (Phytoparasitica, 2015)

Trace element geochemistry of the Mt Vulture carbonatites, southern Italy - Giovanni Mongelli; Michele Paternoster; Giovanna Rizzo; Maria T. Cristi Sansone; Rosa Sinisi (International Geology Review, 2013)

Matrix metalloproteinase-2 (MMP-2) generates soluble HLA-G1 by cell surface proteolytic shedding - Roberta Rizzo; Alessandro Trentini; Daria Bortolotti; Maria C. Manfrinato; Antonella Rotola; Massimiliano Castellazzi; Loredana Melchiorri; Dario Di Luca; Franco Dallocchio; Enrico Fainardi; Tiziana Bellini (Molecular and Cellular Biochemistry, 2013)

Intrathecal Soluble HLA-E Correlates with Disease Activity in Patients with Multiple Sclerosis and may Cooperate with Soluble HLA-G in the Resolution of Neuroinflammation - Fabio Morandi; Consuelo Venturi; Roberta Rizzo; Massimiliano Castellazzi; Eleonora Baldi; Maria Luisa Caniatti; Maria Rosaria Tola; Enrico Granieri; Enrico Fainardi; Antonio Uccelli; Vito Pistoia (Journal of Neuroimmune Pharmacology, 2013)

NKCC2 is activated in Milan hypertensive rats contributing to the maintenance of salt-sensitive hypertension - Monica Carmosino; Federica Rizzo; Patrizia Ferrari; Lucia Torielli; Mara Ferrandi; Giuseppe Bianchi; Maria Svelto; Giovanna Valenti (Pflügers Archiv - European Journal of Physiology, 2011)

Peculiar earthquake damage on a reinforced concrete building in San Gregorio (L’Aquila, Italy): site effects or building defects? - Marco Mucciarelli; Marcello Bianca; Rocco Ditommaso; Marco Vona; Maria Rosaria Gallipoli; Alessandro Giocoli; Sabatino Piscitelli; Enzo Rizzo; Matteo Picozzi (Bulletin of Earthquake Engineering, 2011)

Petrochemical characterization of mafic rocks from the Ligurian ophiolites, southern Apennines - Maria T. Cristi Sansone; Giovanna Rizzo; Giovanni Mongelli (International Geology Review, 2011)

Cyclic influences on the heavy metal chronology in a Central Mediterranean area (Palermo Gulf, Italy) - Salvatore Basile; Maria Brai; Salvatore Rizzo; Marco Spanò; Luigi Tranchina (Journal of Soils and Sediments, 2011)

Trace Elements in Plankton, Benthic Organisms, and Forage Fish of Lake Moreno, Northern Patagonia, Argentina - Maria A. Arribére; Linda M. Campbell; Andrea P. Rizzo; Marina Arcagni; Jorge Revenga; Sergio Ribeiro Guevara (Water, Air, & Soil Pollution, 2010)

Glioma Cell Death: Cell–Cell Interactions and Signalling Networks - H. Anne Leaver; Maria Theresa Rizzo; Ian R. Whittle (Molecular Neurobiology, 2010)

Brain Endothelial Cell Death: Modes, Signaling Pathways, and Relevance to Neural Development, Homeostasis, and Disease - Maria Teresa Rizzo; H. Anne Leaver (Molecular Neurobiology, 2010)

In Vivo Quantification of Helical Blood Flow in Human Aorta by Time-Resolved Three-Dimensional Cine Phase Contrast Magnetic Resonance Imaging - Umberto Morbiducci; Raffaele Ponzini; Giovanna Rizzo; Marcello Cadioli; Antonio Esposito; Francesco De Cobelli; Alessandro Del Maschio; Franco Maria Montevecchi; Alberto Redaelli (Annals of Biomedical Engineering, 2009)

The HLA-G genotype is associated with IL-10 levels in activated PBMCs - Roberta Rizzo; Thomas Vauvert F. Hviid; Marina Stignani; Alessandra Balboni; Maria Teresa Grappa; Loredana Melchiorri; Olavio R. Baricordi (Immunogenetics, 2005)

Structure of the main ganglioside from the brain of Xenopus laevis - Angela Maria Rizzo; Bruno Berra; Federica Rossi; Anna Guerra; Rosalba Gornati; Giovanni Bernardini; Takao Taki; Takeshi Kasama; Laura Mauri; Sandro Sonnino (Glycoconjugate Journal, 2002)

Study on the Sternberg Paradigm in Cirrhotic Patients Without Overt Hepatic Encephalopathy - Piero Amodio; Piergiorgio Marchetti; Franco Del Piccolo; Cristiano Rizzo; Rosa Maria Iemmolo; Lorenza Caregaro; Giorgio Gerunda; Angelo Gatta (Metabolic Brain Disease, 1998)